Utilization of Blepharis sindica herbage in sheep feeding: Effect on nutrient utilization, rumen fermentation and plane of nutrition - BHATT, R S; SAHOO, A; SONI, LALIT KUMAR; SANKHYAN, S K (The Indian Journal of Animal Sciences, 2017)
Rams (36) were fed ad lib. complete feed block (CFB) in 3 groups up to 60 days. Block-1 consisted 35, 60 and 5% of concentrate, cenchrus hay and molasses respectively. In block-2 and block-3 Blepharis sindica herbage was added at 30 and 45%. Dry matter, organic matter, crude protein digestibility increased whereas ADF, cellulose decreased with Blepharis sindica incorporation. Nitrogen balance was higher in block-2 and block-3 fed rams. Total nitrogen, TCA precipitable nitrogen, ammonia level was higher and TVFA lower in SRL of rams fed block-3 and block-2. Microbial protein synthesis / kg of DOMI was higher and dry matter intake was lower in block-2 and block-3 fed rams. Due to better nutrient utilization, higher plane of nutrition and microbial protein synthesis Blepharis sindica herbage can be used in sheep feeding up to 45% after processing as CFB.